Features of the Application of Analytical Procedures in the Audit of Property, Plant and Equipment - Abduxomidovich, Aliyev Sherzod (Research Parks Publishers, 2023)
Methodological aspects of the application of analytical procedures in the audit of property, plant and equipment are studied in the article. As a result of the research, proposals were developed to improve the use of analytical procedures in the audit of property, plant and equipment.